Remote detection of fungal pathogens in viticulture using laser-induced fluorescence: an experimental study on infected potted vines - Kölbl, Christoph; Diedrich, Manu; Ellingen, Elias; Duschek, Frank; Selim, Moustafa; Berkelmann-Löhnertz, Beate (Frontiers in Horticulture, 2023)
Introduction Pathogenic fungi, such as Plasmopara viticola and Erysiphe necator, severely threaten the annual yield of grapes in both quantity and quality. In contrast to other crop production systems, fungicides are intensively applied in viticulture as a countermeasure. The goal of precision viticulture is to optimize vineyard performance as well as the environmental impact by reducing fungicides and applying different techniques and combined strategies. Therefore, new emerging technologies are required, including non-invasive detection, as well as monitoring and tools for the early and in-field detection of fungal development. Methods In this study, we investigated leaves of potted vines (Vitis vinifera cv. ‘Riesling’) and traced the development of the inoculated leaves using our new remote detection system vinoLAS®, which is based on laser-induced fluorescence spectroscopy. We ran a measurement campaign over a period of 17 days. Results We were able to detect a leaf infection with P. viticola, the causal agent of downy mildew, between 5 and 7 days after inoculation. Our results provide evidence for a successful application of laser-based standoff detection in vineyard management in the future. Thus, the vinoLAS system can serve as a model technology for the detection of pathogenic disease symptoms and thus monitoring complete vineyard sites. This allows for early countermeasures with suitable crop protection approaches and selected hot-spot treatments. Discussion As P. viticola is considered one of the most damaging fungi in European viticulture, disease mapping via this monitoring tool will help to reduce fungicide applications, and will, therefore, support the implementation of the European Green Deal claims.